2022
DOI: 10.1109/tns.2022.3142092
|View full text |Cite
|
Sign up to set email alerts
|

High Energy and Thermal Neutron Sensitivity of Google Tensor Processing Units

Abstract: In this paper we investigate the reliability of Google's Coral Tensor Processing Units (TPUs) to both high energy atmospheric neutrons (at ChipIR) and thermal neutrons from a pulsed source (at EMMA) and from a reactor (at TENIS). We report data obtained with an overall fluence of 3.41 × 10 12 n/cm 2 for atmospheric neutrons (equivalent to more than 30 million years of natural irradiation) and of 7.55×10 12 n/cm 2 for thermal neutrons. We evaluate the behavior of TPUs executing elementary operations with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Also, we tested only object detection neural networks, while we explored the reliability of reinforcement learning models. In [24], the authors report the Edge TPU reliability under high energy and thermal neutron radiation. The authors tested several different types of classification and object detection neural networks, while in this work we use the same device and the same radiation type but report the reinforcement learning reliability of 4 different models.…”
Section: Coral Edge Tpumentioning
confidence: 99%
“…Also, we tested only object detection neural networks, while we explored the reliability of reinforcement learning models. In [24], the authors report the Edge TPU reliability under high energy and thermal neutron radiation. The authors tested several different types of classification and object detection neural networks, while in this work we use the same device and the same radiation type but report the reinforcement learning reliability of 4 different models.…”
Section: Coral Edge Tpumentioning
confidence: 99%
“…By performing radiation experiments, recent studies have demonstrated that DNNs accelerators are highly susceptible to transient faults induced by radiation [31], [45]- [47]. Recent research data suggests that while are mostly affected because of the high amount of available resources [48], [49] and the possibility of having multiple output elements corrupted, which undermines DNN reliability [46], [50], FPGAs, are mostly affected due to the programable hardware characteristics, where a transient fault can change the configuration memory and change the circuit [51]- [53].…”
Section: A Motivation and Related Workmentioning
confidence: 99%
“…Software-level [57], [58], [61]- [63], [66]- [91] RTL-level [92], [93] Microarchitectural-level [94] Gate-level [95]- [98] Transistor-level [99], [100] Chip-level [101]- [110] Radiation experiments [81]- [85], [111]- [114] Memristor crossbar-based architectures [115]- [118] oretical study is presented for Feed-Forward Neural Networks (FFNNs) deducing the number of failing neurons and synapses an FFNN can tolerate.…”
Section: Fault Injection Experiments and Frameworkmentioning
confidence: 99%
“…Finally, results on the reliability to neutrons of Google Coral TPU are reported in [114], considering elementary operations and several CNN models. It turns out that, despite the high error rate, most neutron induced errors only slightly modify the convolution output and do not change the detection or classification of CNNs.…”
Section: Fault Injection Experiments and Frameworkmentioning
confidence: 99%